Flow Topology of Three-Dimensional Spherical Flame in Shock Accelerated Flows - Yuejin Zhu; Lei Yu; Gang Dong; Jianfeng Pan; Zhenhua Pan (Advances in Materials Science and Engineering)
The flow topologies of compressible large-scale distorted flames are studied by means of the analysis of the invariants of the velocity gradient tensor (VGT). The results indicate that compressibility plays a minor role in the distorted flame zone. And the joint probability density function (p.d.f.) of the Q-R diagram appears as a teardrop shape, which is a universal feature of turbulence. Therefore, the distorted flame exhibits the characteristic of large-scale turbulence combustion, especially behind the reflected shock wave, while the p.d.f. of the QS⁎-QW diagram implies that the dissipation is enhanced in the compression and expansion regions, where it is higher than that when P=0. Furthermore, we identify that the flame evolution is dominated by rotation by means of a quantitative statistical study, and the SFS topology is the predominant flow pattern. Not surprisingly, negative dilatation could suppress the unstable topologies, whereas positive dilatation could suppress the stable topologies.